(untitled) (Don Bosco Institute of Technology Delhi Journal of Research, 2026)
The automobile industry is undergoing a fundamental strategic inflection: the convergence of accelerating climate change awareness, tightening regulatory standards, and a structural shift in consumer values has transformed green marketing from a peripheral promotional exercise to a core strategic imperative. This research examines the influence of green marketing strategies on consumer behavior, brand perception, competitive dynamics, and sustainable innovation within the automobile sector, with particular focus on the Indian market context and cross-national comparative evidence from global automotive leaders. Employing a mixed-methods design grounded in an inductive research philosophy, the study integrates primary survey data collected from 100 urban, environmentally aware consumers — including students, working professionals, and active vehicle users — with secondary data triangulated across corporate sustainability reports (Tesla, Toyota, BMW, Maruti Suzuki), industry analyses (SIAM, JATO Dynamics), peer-reviewed academic literature, and regulatory policy documents. The theoretical framework synthesizes the Theory of Planned Behavior (Ajzen, 1991), the Green Marketing Mix framework, Legitimacy Theory (Suchman, 1995), and Brand Equity theory (Keller, 1993) to analyze the mechanisms through which green marketing creates consumer value and competitive advantage. Key findings indicate that 68% of respondents incorporate environmental considerations into vehicle purchase decisions; that brands with credible green positioning — Tesla, Toyota, and BMW — demonstrate significantly higher consumer trust and recall; and that the majority of respondents express willingness to pay a moderate price premium for verified eco-friendly vehicles. EV and hybrid adoption in India reached 19.23% of total passenger vehicle sales in 2023–24 (JATO Dynamics), reflecting the commercial impact of sustained green marketing investment. The study also examines greenwashing as a structural market failure with severe reputational and regulatory consequences, and proposes a multi-level countermeasure framework for manufacturers. The research contributes to the emerging literature on green marketing in the automotive sector by providing India-contextualized empirical evidence, developing a practical Green Marketing Strategic Framework, and generating a differentiated research agenda. It concludes with actionable recommendations for automobile manufacturers, marketing managers, and policy makers seeking to align commercial strategy with environmental imperatives.